A perspectiva da governança colaborativa no contexto da crise: o aprendizado da Pandemia Covid-19 - Silva, Iza Leilla Carlos da (2022)
With the Covid-19 pandemic, the whole world had to readapt to a relatively unknown scenario of what it was used to. Governments needed to respond to the crisis in an agile and adaptive way in order to reduce the negative impacts generated for society. In the Brazilian states, each government has different characteristics, Rio Grande do Norte had one of the highest lethality rates in the northeast region, so this research started from the following question: How has Rio Grande do Norte been adopting strategies to combat the Covid-19 pandemic? Its general objective was to analyze the perspectives of collaborative governance of the government of the state of Rio Grande do Norte in relation to the Covid-19 pandemic. Content analysis was performed on the electronic portals of laboratory Lais, CoronavirusRN, RegulaRN and on the Covid-19 portal, which were created by the state government of Rio Grande do Norte to explain the data of the epidemiological crisis until reaching theoretical saturation, in the period of 2019 to 2021, data were compiled with the help of Atlas.ti® software. The government monitored the data using advanced technology, following the population in social isolation, beds occupied by patients, level of mortality, etc. of local health. It is possible to conclude that Rio Grande do Norte has adopted collaborative governance in all aspects related to resources, technology, communication, infrastructure organization, control, regulation, public participation, compliance and collaboration, as it complies with all stages of Huang's model ( 2020), being able to enable the state government to make quick and assertive decision-making, as well as analyze the capacity to manage the pandemic crisis and provide the federal government with information.